DAMPAK GAYA KEPEMIMPINAN TERHADAP LOYALITAS KARYAWAN DAN TURNOVER INTENTION (STUDI KASUS PT BANK XYZ TBK) - Kezia Adeline (Jurnal Bina Manajemen, 2022)
The Indonesian banking industry had a voluntary turnover rate in 2019, this could indicate a low level of employee loyalty in Indonesian banking. This research was conducted using qualitative research methods and semi-structured interview questions. There were a total of thirteen interviewees, twelve employees and a senior human resources manager who worked at PT Bank XYZ as a triangulation process. Thematic data analysis was used to analyze the data. The results of the interview show that the leadership style has a high leadership style and has a maximum effect on employee loyalty and turnover intention at PT Bank XYZ. Transformational leadership style and democratic leadership style are the most suitable leadership styles to increase employee loyalty and reduce turnover intention of employees working at PT Bank XYZ. In addition, the results of the interview show that there are eight main factors that influence employee loyalty and turnover intention of employees working at PT Bank XYZ. The eight main factors are: Work-Life Balance, Passion for Job, Salary, Bonuses and Benefits, Relationship with Leader, Relationship with Team Members, Leader Appreciation and Respect, Career Path, and Personal Development. From the results of thestudy, it can be concluded that leadership style is the most important and important factor influencing employee loyalty and turnover intention as stated by interviewees. Transformational and democratic leadership styles are the most suitable leadership styles to increase employee loyalty and reduce turnover intentions at PT Bank XYZ.